Pengaruh Penggunaan Aplikasi Wordwall Terhadap Hasil Belajar Matematika Siswa Kota Parepare - Rofinus Badung; Asdar Dollo (Tautologi: Journal of Mathematics Education, 2024)
This study aims to determine the positive effect of using the wordwall on the mathematics learning outcomes of class VIII UPTD SMP Negeri 2 Parepare students. This type of research is quasi-experimental. The population of this research is class VIII UPTD SMP Negeri 2 Parepare for the academic year 2022/2023 which consists of ten classes, namely VIII 1, VIII 2, VIII 3, VIII 4, VIII 5, VIII 6, VIII 7, VIII 8, VIII 9 and VIII 10. The total sample in this study was 32 students of class VIII 1 UPTD SMP Negeri 2 Parepare who were selected using the cluster random sampling technique. The research data was obtained by using a test sheet and a questionnaire sheet. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of the study indicate that there is a positive influence on the use of the wordwall on the mathematics learning outcomes of class VIII UPTD SMP Negeri 2 Parepare students. This is indicated by the mastery of student learning included in the "High" category with an average value of 83.50 which classically reached 93.70% of students who had completed, and student responses to learning mathematics using the Wordwall is positive with an average percentage of 83.28 and the calculation of inferential statistics for gain using a one-sample t-test shows a significant level of < (0.000 < 0.05).